On Some Functional-Stylistic Peculiarities of the Language of Religion - Gasparyan, Naira; Ajamoghlyan, Arevik (Armenian Folia Anglistika, 2009)
Research on the functional-stylistic belonging of different religions has become quite actual. The article examines issues related to this sphere. An attempt has been made to determine important functional-stylistic characteristics of the language of religion through the research of the interrelation of various religions, common language symbols, similarities in the way of thinking of people having different religions, as well as the expressive language and other linguistic phenomena. This can shed light on certain phenomena in this sphere that have not been investigated yet.